DETERMINANTS OF BUDGET ABSORPTION IN REGIONAL APPARATUS THROUGHOUT EAST NUSA TENGGARA - Ardini Hartarti Ngongo; Henny Rahyuda (Adisam Publisher, 2025)
Budget absorption targets that are not properly absorbed will trigger idle funds and eliminate the benefits of spending, so attention is needed from each regional apparatus. This research aims to determine the determinants of budget absorption in regional apparatus throughout East Nusa Tenggara. The samples in this research are financial management officials who are directly related to budget planning, budget implementation and budget absorption, namely: Budget Users (PA), Technical Implementing Officials (PPTK), and Expenditure Treasurer. The sample selection technique was purposive sampling, totaling 207 respondents. This research uses a quantitative approach, with primary data in the form of a questionnaire in the form of a Google Form platform. The analytical method used in this research is Structural Equation Modeling Partial Least Square (SEM) using the Partial Least Square (PLS) approach using SmartPLS 4.0 software. The research results show that budget planning, budget implementation, procurement of goods and services, and management commitment have a positive effect on budget absorption. While human resource competency has a negative effect on budget absorption. The results of the respondents' descriptions found that the most prominent budget absorption problem in Regional Devices throughout East Nusa Tenggara was the placement of financial management officials who did not match their competencies. Although the competencies they have are high, the placement of financial management officials who do not match their competencies has an impact on low communication skills so that there is no effective coordination between fields, which has an impact on low budget absorption.